Female labor force intermittency and current earnings: a switching regression model with unknown sample selection - Julie L. Hotchkiss; M. Melinda Pitts (Federal Reserve Bank of Atlanta, 2003)
Using the Health and Retirement Survey, this paper finds a 16 percent selectivity-corrected wage penalty among women who engage in intermittent labor market activity. This penalty is experienced at a low level of intermittent activity but appears not to play an important role in a woman's decision to undertake such activity. In addition, employer preferences appear to play a larger role than human capital atrophy in the determination of the wage penalty.
Keywords: 330